2019
DOI: 10.1186/s12942-019-0176-x
|View full text |Cite
|
Sign up to set email alerts
|

Methodological approaches to the study of cancer risk in the vicinity of pollution sources: the experience of a population-based case–control study of childhood cancer

Abstract: Background Environmental exposures are related to the risk of some types of cancer, and children are the most vulnerable group of people. This study seeks to present the methodological approaches used in the papers of our group about risk of childhood cancers in the vicinity of pollution sources (industrial and urban sites). A population-based case–control study of incident childhood cancers in Spain and their relationship with residential proximity to industrial and urban areas was designed. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Importantly, MC generally has highly harmful levels of air pollution ( 152 155 ) due to its geographic, climatic, and social conditions ( 49 , 156 ). Prior studies have reported that living in an urban area or near an industrial zone ( 157 – 159 ) and being exposed to either vehicular traffic ( 160 ) or benzene derivatives ( 161 , 162 ), are factors potentially contributing to the development of childhood AL ( 126 , 163 166 ). On the other hand, we observed a relatively lower AL incidence rates in the municipalities located south and east of MC, such as Milpa Alta, Xochimilco, and Tláhuac, which are characterized by preserved areas of agricultural land production ( 60 – 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, MC generally has highly harmful levels of air pollution ( 152 155 ) due to its geographic, climatic, and social conditions ( 49 , 156 ). Prior studies have reported that living in an urban area or near an industrial zone ( 157 – 159 ) and being exposed to either vehicular traffic ( 160 ) or benzene derivatives ( 161 , 162 ), are factors potentially contributing to the development of childhood AL ( 126 , 163 166 ). On the other hand, we observed a relatively lower AL incidence rates in the municipalities located south and east of MC, such as Milpa Alta, Xochimilco, and Tláhuac, which are characterized by preserved areas of agricultural land production ( 60 – 62 ).…”
Section: Discussionmentioning
confidence: 99%
“… 2–7 Recently studies also showed that air pollution predisposed the public to a higher risk of breast cancer and childhood leukaemia, apart from lung cancer. 8 , 9 Besides, air pollution is estimated to contribute to 7 million deaths worldwide in 2016. 1…”
Section: Introductionmentioning
confidence: 99%
“…This will also make it possible to continue using GIS to perform cluster analyses and explore spatial dependence in the distribution of cancer cases. The extensive information available can also be used for further multivariate analysis of childhood cancer incidence with associated variables such as family income, cancer type, and environmental exposures [70].…”
Section: Discussionmentioning
confidence: 99%